(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The nearctic aphid Ericaphis scammelli (Mason) has been recently detected in Piedmont, a NW region of Italian peninsula, infesting cultivated blueberries (Vaccinium corymbosum, V. ashei and their hybrids) and cranberry (V. macrocarpon). Details and figures are given on the aphid morphology, adding short notes on its taxonomy, geographical distribution, host plants and biology. In the investigated area this aphid species is holocyclic, overwintering as eggs, laid on twigs of its host plants as well as on leaves. Damages and control measures are also discussed.